Consumer Preferences on Halal Supply Chain Implementation in Food and Beverage Franchise Firms in Mataram City - Yusuf, M Syahdi; Rahman, Fuad Arif (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to determine consumer preferences for the implementation of halal supply chains in food and beverage franchise firms in Mataram City. Customer preference theory is measured using the hierarchy of effect model. The object of research is the society of Mataram City. The research method uses multiple linear regression analysis and partial test (t-test) to answer the research hypothesis. The sampling technique used was purposive sampling method with a total of 384 respondents determined based on the Krejcie and Morgan table. Research data management was carried out using IBM SPSS 25. Data collection was carried out using an online questionnaire. The results of this study reveal that the variables of customer awareness, customer liking, customer preference have a significant effect on the implementation of halal supply chains in food and beverage franchise companies. Meanwhile, customer purchase has an effect but not significant halal supply chain implementation in food and beverage franchise companies. Meanwhile, customer knowledge and customer conviction / intention to buy have no effect on the implementation of the HSCM in food and beverage franchise firms. The results of this study will be useful for food and beverage franchise companies, knowledge for readers and can be a source of information and reference for further research.